2013
DOI: 10.1007/s40502-013-0010-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nitrate uptake and assimilation in wheat seedlings grown under elevated CO2

Abstract: Wheat (Triticum aestivum L.) cv PBW 343 was grown in Hoagland solution devoid of nitrogen (-N) under two CO 2 levels viz. ambient (380 lL L -1 , AC) and elevated (600 ± 50 lL L -1 , EC) for 20 days in growth chambers. The rate of uptake, assimilation and accumulation of nitrate was compared. At lows nitrate concentration up to 0.5 mM, rate of nitrate uptake was higher in EC grown seedlings as compared to AC. Under non-limiting supply of external nitrate, the rate of uptake declined in EC grown seedlings. Nitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…Conversely, some researchers observed the opposite effect of CO 2 enrichment on NR activity, under high nitrate conditions; Geiger et al 6 reported that elevated CO 2 slightly stimulated NR activity in the leaves of tobacco plants fed with 2 mM nitrate, while causing an approximately 30% decrease in leaf NR activity in plants fed with a 6 mM nitrate supply. This result is similar to that of Lekshmy et al, 22 in which CO 2 enrichment increased NR activity (by 11%-24%) in the leaves of wheat seedlings grown in low nitrate conditions (<2 mM), but the opposite occurred when the plants were grown in high nitrate conditions (>5 mM). These findings imply that the effect of elevated CO 2 on NR activity in plants is dependent on the nitrate levels in the growth medium; this was confirmed by our latest report: in low-level nitrate supply conditions, NR activity is stimulated by the basal endogenous nitric oxide (NO) and the NO induced by CO 2 enrichment, via an NOS-dependent pathway.…”
supporting
confidence: 91%
“…Conversely, some researchers observed the opposite effect of CO 2 enrichment on NR activity, under high nitrate conditions; Geiger et al 6 reported that elevated CO 2 slightly stimulated NR activity in the leaves of tobacco plants fed with 2 mM nitrate, while causing an approximately 30% decrease in leaf NR activity in plants fed with a 6 mM nitrate supply. This result is similar to that of Lekshmy et al, 22 in which CO 2 enrichment increased NR activity (by 11%-24%) in the leaves of wheat seedlings grown in low nitrate conditions (<2 mM), but the opposite occurred when the plants were grown in high nitrate conditions (>5 mM). These findings imply that the effect of elevated CO 2 on NR activity in plants is dependent on the nitrate levels in the growth medium; this was confirmed by our latest report: in low-level nitrate supply conditions, NR activity is stimulated by the basal endogenous nitric oxide (NO) and the NO induced by CO 2 enrichment, via an NOS-dependent pathway.…”
supporting
confidence: 91%
“…Elevated CO 2 inhibits shoot nitrogen assimilation in C3 plants through two different mechanisms: (1) elevated CO 2 inhibits nitrite transport into chloroplasts; (2) elevated CO 2 inhibits the photorespiration process (Bloom et al 2010). Photorespiration stimulates the export of malate from the chloroplast into the cytoplasm, and this malate generates the NADH used to reduce nitrate to nitrite (Bloom et al 2010(Bloom et al , 2012Aranjuelo et al 2013;de la Mata et al 2013;Lekshmy et al 2013;Bloom 2015). Elevated CO 2 with limited N availability disrupts plant growth and gives rise to senescence progression, indicated by chlorosis, anthocyanin accumulation, and increased GS1 expression (de la Mata et al 2013;Aoyama et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The uptake amount and N contribution of glycine under eCO 2 conditions were significantly higher than those under aCO 2 conditions, while the absorption and N contribution of ammonium and nitrate were generally lower. Several studies have shown that eCO 2 inhibits the uptake of nitrate in environments with a single N source (nitrate) (Bloom et al ) and in the mixed field community (Shimono and Bunce , Lekshmy et al ). Reduced nitrate uptake under eCO 2 conditions may result from the limited nitrate reductase activity (Lekshmy et al ) and further N metabolism (Bloom et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that eCO 2 inhibits the uptake of nitrate in environments with a single N source (nitrate) (Bloom et al ) and in the mixed field community (Shimono and Bunce , Lekshmy et al ). Reduced nitrate uptake under eCO 2 conditions may result from the limited nitrate reductase activity (Lekshmy et al ) and further N metabolism (Bloom et al ). Furthermore, the enhanced absorption of glycine might decrease the absorption of nitrate, and increases of root ammonium or amino acid content could induce feedback regulation of nitrate absorption (Thornton and Robinson ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation